MULTIFOCAL IMAGES FUSION - Ondrej KOVÁČ; Iveta GLADIŠOVÁ (Acta Electrotechnica et Informatica, 2017)
The paper deals with the issue of multifocal image fusion. Two techniques of the hierarchical image representation are analyzed herein. The first one is hierarchical decomposition based on the Laplacian pyramid and the second one is based on integer discrete wavelet transformation. After the analysis of the above-mentioned decompositions techniques the algorithm of multifocal image fusion is described. Attention is given to the detection of the focused parts of approximated images. From the detected parts, the approximation of an image is obtained. The analyzed algorithm is experimentally verified and the accuracy with regard to the decomposition method and level of decomposition is evaluated. The fusion is done with real microscopic images.